MERAWAT JIWA DI TENGAH ZAMAN YANG RETAK: URGENSI TEOLOGI, PASTORAL, DAN PENDIDIKAN DALAM ISU KESEHATAN MENTAL - Yustina Madya Marampa (Diegesis : Jurnal Teologi, 2024)
This study examines mental health as an urgent field of theological, pastoral, and educational reflection within contemporary Christian faith. In response to the growing global mental health crisis, this study argues that mental suffering should not be reduced merely to a medical disorder or a weakness of faith, but should be understood as an existential and theological experience that touches human relationships with the self, others, community, and God. This study aims to formulate a holistic framework for understanding mental health from a Christian perspective through the integration of biblical studies, theology of suffering, pastoral ministry, and Christian education. This research employs a qualitative approach using literature study and interdisciplinary theological analysis. The findings indicate that biblical narratives provide space for human experiences of fragility, lament, trauma, and despair, while also revealing a pattern of divine accompaniment that is empathetic, relational, and gradual. These findings encourage the transformation of the church’s pastoral paradigm from normative and stigmatizing approaches toward hospitality, trauma-informed care, mental health literacy, and collaboration with professional caregivers. Furthermore, Christian education plays a strategic role in shaping the mental and spiritual resilience of younger generations through a reflective, contextual, and psychosocially sensitive curriculum. Therefore, churches and Christian educational institutions need to develop an integrative and compassionate ecosystem of healing rooted in the hope of faith.